ByzRev 06.2024.066: Paul Magdalino, Roman Constantinople in Byzantine Perspective.: The Memorial and Aesthetic Rediscovery of Constantine’s Beautiful City, from Late Antiquity to the Renaissance (Brill Research Perspectives in Byzantine Studies). Leiden – Boston: Brill 2024. - Berger, Albrecht (The Byzantine Review, 2024)
Paul Magdalino, Roman Constantinople in Byzantine Perspective. The Memorial and Aesthetic Rediscovery of Constantine’s Beautiful City, from Late Antiquity to the Renaissance (Brill Research Perspectives in Byzantine Studies). Leiden – Boston: Brill 2024. VI, 169 pp. – ISBN 978-90-04-69889-5 (paperback), 978-90-04-70076-5 (e-book)